Scientific and Experimental Justification for the Industrial Application of Accelerated Electrochemical Methods for Testing Resistance to Intergranular Corrosion - Derhach, T.О.; Sukhomlyn, D.A.; Hlushkova, D.B.; Baliev, A.Ye. (Ukrainian State University of Science and Technologies, Dnipro, 2025)
ENG: The purpose of this work is to provide a scientific and experimental justification for the widespread industrial application of accelerated electrochemical methods for testing the resistance of austenitic stainless steel products to intergranular corrosion as an alternative to prolonged (up to 240 hours) boiling tests in acid solutions. A large-scale comparative study was conducted using standardized methods for assessing the intergranular corrosion resistance: (a) in weakly oxidizing environments – an accelerated electrochemical method of potentiostatic etching in 1 N HClO4+0.25 N NaCl, compared with a prolonged test involving the boiling of samples in 35% H2SO4 with the addition of CuSO4 and metallic copper (Practice E, ASTM A-262); and (b) in highly oxidizing environments – an accelerated electrochemical method of anodic etching of metallographic sections in 10% H2C2O4 ⋅2H2O, compared with a prolonged test involving the boiling of samples in 65% HNO3 (Practices A and C, ASTM A-262, respectively). The study was conducted on experimental 304L-type stainless steel samples with a carbon content of 0.018–0.05%, sensitized under different conditions, as well as on industrially manufactured Cr–Ni and Cr–Ni–Mo stainless steel products. A strong correlation was found between the results obtained using the proposed accelerated methods and the traditional prolonged tests. Additionally, quantitative criteria for satisfactory intergranular corrosion resistance were established when testing by the potentiostatic etching and Practice A methods. The study demonstrated the high corrosion resistance of special Σ3 twin grain boundaries when using method A, as described in the coincident site lattice theory. The obtained results support the recommendation of using the accelerated potentiostatic etching and Practice A methods as viable alternatives to prolonged testing procedures in industrial production of austenitic stainless steel products.

UKR: Мета даної роботи є наукове та експериментальне обґрунтування можливості широкого застосування в промисловості прискорених електрохімічних методів випробування на стійкість до міжкристалітної корозії металопродукції з аустенітних нержавіючих сталей як альтернативи тривалим (до 240 годин) методам кип’ятіння зразків у розчинах кислот. Було здійснено масові порівняльні випробування на стійкість до міжкристалітної корозії за двома типами методик: а) у слабко окисних середовищах – прискореним електрохімічним методом потенціостатичного травлення зразків у 1 N НClO4+0,25 N NaCl та тривалим методом шляхом кип’ятіння зразків у 35% H2SO4 з додаванням CuSO4 і металевої міді (Практика Е, ASTM A-262); б) у сильно окисних середовищах – прискореним електрохімічним методом анодного травлення металографічних шліфів у 10% H2C2O4 2H2O та тривалим кип’ятінням зразків у 65% HNO3 (Практики А і С, ASTM A-262, відповідно). Для досліджень використовували зразки сталі типу 304L (0.018–0.05% С), сенсибілізовані за різними режимами, а також металопродукцію з Cr–Ni та Cr–Ni–Mo сталей промислового виробництва. Встановлено збіжність результатів випробувань зразків, отриманих запропонованими прискореними і традиційними тривалими методами, а також визначено кількісні критерії задовільної стійкості сталей до міжкристалітної корозії при випробуванні за методами потенціостатичного травлення і Практики А. Показана висока корозійна стійкість спеціальних двійникових меж зерен 3 у рамках теорії решіток співпадаючих вузлів. Отримані результати дозволяють рекомендувати застосування прискорених методів потенціостатичного травлення та Практики А замість тривалих методик у промисловому виробництві металопродукції з аустенітних нержавіючих сталей.
Наукове та експериментальне обґрунтування застосування в промисловості прискорених електрохімічних методів випробування на стійкість до міжкристалічної корозії
Keywords: austenitic stainless steels; intergranular corrosion; electrochemical methods; grain boundary structure; special boundaries; coincident site lattices; аустенітні нержавіючі сталі; міжкристалітна корозія; електрохімічні методи; зерногранична структура; спеціальні межі; решітки співпадаючих вузлів; КТНР; NATURAL SCIENCES; Chemistry; TECHNOLOGY